Tomato POLLEN DEFICIENT 2 encodes a G-type lectin receptor kinase required for viable pollen grain formation. (19th October 2022) - Micol-Ponce, Rosa; García-Alcázar, Manuel; Lebrón, Ricardo; Capel, Carmen; Pineda, Benito; García-Sogo, Begoña; Alché, Juan de Dios; Ortiz-Atienza, Ana; Bretones, Sandra; Yuste-Lisbona, Fernando Juan; Moreno, Vicente; Capel, Juan; et al.
Abstract: Pollen development is a crucial biological process indispensable for seed set in flowering plants and for successful crop breeding. However, little is known about the molecular mechanisms regulating pollen development in crop species. This study reports a novel male-sterile tomato mutant, pollen deficient 2 ( pod2 ), characterized by the production of non-viable pollen grains and resulting in the development of small parthenocarpic fruits. A combined strategy of mapping-by-sequencing and RNA interference-mediated gene silencing was used to prove that the pod2 phenotype is caused by the loss of Solanum lycopersicum G-type lectin receptor kinase II.9 (SlG-LecRK-II.9) activity. In situ hybridization of floral buds showed that POD2/SlG-LecRK-II.9 is specifically expressed in tapetal cells and microspores at the late tetrad stage. Accordingly, abnormalities in meiosis and tapetum programmed cell death in pod2 occurred during microsporogenesis, resulting in the formation of four dysfunctional microspores leading to an aberrant microgametogenesis process. RNA-seq analyses supported the existence of alterations at the final stage of microsporogenesis, since we found tomato deregulated genes whose counterparts in Arabidopsis are essential for the normal progression of male meiosis and cytokinesis. Collectively, our results revealed the essential role of POD2/SlG-LecRK-II.9 in regulating tomato pollen development. Abstract : POD2 encodes a tomato G-type lectin receptor kinase vital for functional pollen formation. The loss of POD2 function impairs meiosis and tapetum degradation, resulting in male sterility and parthenocarpy.